Prevalence of wasting, overweight and obesity among children under 5 years in 10 cities of Jiangsu Province: a multi-center cross-sectional study - Li, Lihua; Bu, Hemei; Zheng, Wen; Ni, Yufei; Wu, Aiping; Ye, Kan; Jiang, Xinye; Yang, Guoqiang; Liu, Guoqin; Bao, Yelin; Zhang, Li; Qi, Hongxia; et al. (Frontiers in Nutrition, 2026)
ObjectiveTo understand the current epidemiological status and influencing factors of wasting, overweight and obesity among children under 5 years old in Jiangsu Province, thereby providing a scientific basis for developing early strategies.MethodsA multi-center, stratified cluster random sampling approach was employed to investigate birth status, season variation, regional differences and other relevant factors among children under 5 years in Jiangsu Province from April 2014 to March 2015.ResultsA total of 5,289 children were initially enrolled in this study. After applying strict inclusion and exclusion criteria, 4,420 children were included in the statistical analysis (2,303 boys and 2,117 girls). The prevalence of wasting, risk of overweight, overweight and obesity were 1.403, 17.583, 4.594, and 1.426%, respectively. Firstly, the prevalence of wasting was relatively higher in children in rural areas, aged 24–35 months, born via spontaneous delivery, with a birth weight <2,500 g, and investigated in summer and central Jiangsu areas, with prevalence rates of 1.776, 2.009, 1.692, 1.923, 2.070 and 2.760%, respectively. All cities in Jiangsu Province except Nanjing were associated with wasting. Secondly, the prevalence of risk of overweight was higher among boys, infants aged 0–11 months, preterm infant, born with birth weight ≥4,000 g, investigated in winter, with prevalence rates of 19.236, 24.583, 21.304, 23.029 and 24.481%, respectively. And boys, all age groups except 48–59 months, birth weight ≥4,000 g, investigated in spring and winter were factors associated with risk of overweight. Thirdly, the prevalence of overweight was higher among boys, infants aged 0–11 months, birth weight ≥4,000 g, investigated in winter, with prevalence of 5.471, 7.292, 7.884, and 8.605%, respectively. And boys, 0–11 months, birth weight ≥4,000 g, investigated in spring and winter were factors associated with overweight. Finally, the prevalence of overweight among children with boys, 36–47 months, birth weight ≥4,000 g, investigated in winter, and southern of Jiangsu Province were 1.824, 2.039, 2.075, 2.533 and 1.727%, respectively. And boys were factors associated with obesity.\.ConclusionThe historical prevalence of wasting, overweight and obesity among children under 5 years in Jiangsu Province remain at a low level.